Method for producing silicon composite material and negative electrode sheet containing the same

A silicon/carbon nanotube/silicon oxide/lithium oxide/lithium silicate composite material addresses the expansion and efficiency issues in silicon-based batteries by forming a three-dimensional network structure, improving cycle stability and conductivity, thus enhancing battery performance and energy density.

JP7614325B2Active Publication Date: 2025-01-15SHANGHAI RUIPU ENERGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023503224
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-24
Filing Date
2021-12-02
Publication Date
2025-01-15
Estimated Expiration
2041-12-02

AI Technical Summary

Technical Problem

Existing silicon-based composite materials for batteries face issues with rapid volumetric expansion due to lithium insertion, leading to poor cycle stability and low initial efficiency, as silicon oxide reacts with lithium ions, consuming irreversible byproducts and reducing battery performance.

Method used

A silicon/carbon nanotube/silicon oxide/lithium oxide/lithium silicate composite material is manufactured by specific particle size ratios and processing steps, including high-temperature carbonization, ball-milling, and lithium replenishment, forming a three-dimensional network structure that suppresses expansion and maintains conductivity.

Benefits of technology

The composite material achieves high gram capacity, excellent cycle stability, and low volumetric expansion, enhancing battery performance and energy density without requiring additional carbon coating steps, making it suitable for automotive applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007614325000002
    Figure 0007614325000002
  • Figure 0007614325000003
    Figure 0007614325000003
  • Figure 0007614325000004
    Figure 0007614325000004
Patent Text Reader

Abstract

The present invention discloses a method for producing a silicon composite material and a negative electrode sheet containing the same, which relates to the field of silicon-based composite materials. The silicon-based composite material includes silicon nanoparticles (1), carbon nanotubes (2), silicon oxide, lithium oxide, and lithium silicate, where the carbon nanotubes (2) and the silicon nanoparticles (1) are dispersed and cross-linked to form a three-dimensional network structure, and the silicon oxide, lithium oxide, and lithium silicate coat the three-dimensional network structure to form secondary particles. By uniformly coating these silicon secondary particles and graphite at a specific particle size ratio, a silicon-containing negative electrode sheet can be produced that exhibits high capacity development, excellent conductivity, high Coulombic efficiency, small volume expansion, and excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of silicon-based composite materials, and to a method for producing a silicon composite material and a negative electrode sheet containing the same, and more particularly to a silicon / carbon nanotube / silicon oxide / lithium oxide / lithium silicate composite material and a negative electrode sheet containing the same. [Background technology]

[0002] With the widespread use of new energy vehicle batteries and the continuing demand from consumers for longer driving range, further increasing the energy density of batteries has become key. Silicon has the advantages of high gram capacity (>3000mAh / g), abundant resources, and low potential to lithium, making it a popular alternative to graphite. However, when silicon expands due to lithium insertion, it experiences a rapid volume expansion (about 300%), which results in poor cycle stability. Research has revealed that silicon nanoparticles can be coated with silicon oxide to form secondary particles, which can block direct contact between the electrolyte and silicon, and silicon oxide can suppress the expansion of silicon particles. However, secondary particles can still be crushed in the later stages of cycling, which can cause silicon to come into direct contact with the electrolyte at the new fracture interface, resulting in side reactions and worsening the cycle.

[0003] To solve the above problems, patent CN107658452 proposes a silicon / carbon nanotube / silicon carbon oxide composite material that uses carbon nanotubes to strengthen the bonds between silicon nanoparticles and maintain the stability of secondary particles. However, the silicon oxide in this composite reacts with lithium ions when the battery first inserts lithium to generate irreversible by-products, lithium oxide and lithium silicate. These by-products consume a large amount of lithium, causing the initial efficiency (initial charge / discharge efficiency) of the battery to be too low. Therefore, improving the initial efficiency while suppressing the volume expansion of silicon materials is an issue that needs to be resolved as soon as possible. Summary of the Invention [Problem to be solved by the invention]

[0004] In view of the above, the object of the present invention is to provide a method for producing a silicon composite material and a negative electrode sheet containing the same. The present application provides a silicon / carbon nanotube / silicon oxide / lithium oxide / lithium silicate composite material that exhibits high gram capacity (capacity per gram) of silicon, suppresses expansion of silicon due to lithium insertion, and improves the electrical conductivity of silicon while maintaining high initial efficiency. This silicon composite material (silicon / carbon nanotube / silicon oxide / lithium oxide / lithium silicate composite material) and graphite are slurried at a specific particle size ratio to produce a negative electrode sheet, which has high capacity expression, excellent electrical conductivity, high Coulombic efficiency, small volume expansion, and high cycle stability. [Means for solving the problem]

[0005] The object of the present invention is achieved by the following technical solutions:

[0006] In a first aspect, the present invention provides a method for producing a negative electrode sheet containing the silicon composite material, the negative electrode sheet further containing graphite, and a particle size ratio of the silicon composite material to the graphite is 1:10 to 1:5; S1, adding silicon nanoparticles, carbon nanotubes, a silane coupling agent and a dispersant to an organic solvent, stirring uniformly, and spray-drying to obtain a mixed powder, and then carbonizing the mixed powder at high temperature and ball-milling to obtain a silicon / carbon nanotube / silicon-oxygen composite; S2, activating the silicon / carbon nanotube / silicon-oxygen composite, mixing the activated silicon / carbon nanotube / silicon-oxygen composite with a lithium source, ball milling to obtain a mixture, heat-treating the mixture, and classifying the heat-treated mixture to obtain the secondary particles, i.e., the silicon composite material; S3: mixing the silicon composite material with graphite, conductive carbon and a polyacrylic acid emulsion to prepare a slurry, applying the slurry to a negative electrode current collector, roll pressing the slurry, and drying the slurry under high temperature and vacuum to prepare a negative electrode sheet.

[0007] In one embodiment of the present invention, in step S1, the silane coupling agent is any one of di(alkyleneimino)alkenylmethylsilane, alkyleneiminoalkenyldimethylsilane, aryleneiminoalkenyldimethylsilane, tris(alkyleneimino)alkenylsilane, diarylaminoalkenyldimethylsilane, di(aryleneimino)alkenylmethylsilane, di(diarylamino)alkenylmethylsilane, and tris(aryleneimino)alkenylsilane.

[0008] In one embodiment of the present invention, in step S1, the dispersant is polyethylene glycol having a weight average molecular weight in the range of 800-5000.

[0009] In one embodiment of the present invention, in step S1, the organic solvent is one or a mixture of carbon tetrachloride, N-methylpyrrolidone, acetone, diphenylamine, toluene, and diethanol.

[0010] As one embodiment of the present invention, in step S1, the high-temperature carbonization temperature is set to 300 to 700° C., and the carbonization time at this temperature is set to 3 to 7 hours.

[0011] In step S1, the weight ratio of the silicon nanoparticles, carbon nanotubes, silane coupling agent, dispersant, and organic solvent is (1-5):(0.01-0.05):(1-5):(0.1-1):100.

[0012] In one embodiment of the present invention, in step S2, the activation step includes uniformly mixing an activator with the silicon / carbon nanotube / silicon-oxygen composite, and the uniformly mixed product is dried and heat-treated, and then cooled to room temperature under gas protection.

[0013] In one embodiment of the present invention, the activator contains one or more of 0.1-3M HF, 0.1-1M HCl, 0.1-1M sodium nitrate, and 0.1-1M potassium permanganate.

[0014] In one embodiment of the present invention, the drying and heat treatments are carried out at a drying temperature of 60 to 100° C., for a drying time of 6 to 10 hours, and at a heat treatment temperature of 500 to 800° C. time is 5 to 10 hours.

[0015] In one embodiment of the present invention, in step S2, the lithium source comprises a solid-phase and / or liquid-phase lithium source, the liquid-phase lithium source comprising at least one of lithium sulfate, lithium nitrate, and lithium halide.

[0016] In one embodiment of the present invention, in step S2, the heat treatment step is performed under vacuum at a temperature of 2500 to 4500°C for 1 to 2 hours. In the system of the present invention, due to the influence of carbon nanotubes, the vacuum temperature is too low and the heat-keeping time is too short, so that the lithium source cannot fully react with the silicon / carbon nanotube / silicon-oxygen composite, and the resulting composite particles have problems such as high charge gram capacity, low initial efficiency, poor cycle, and large expansion. By setting a certain heat-keeping time, the stress relaxation of the carbon nanotubes in the composite particles can be promoted and they can be dispersed more uniformly. However, if the heat-keeping time is too long, the particle size of the silicon element in the composite increases, the local expansion after lithium insertion increases, and the particle crushing cycle becomes poor.

[0017] In one embodiment of the present invention, in step S2, the classification step is carried out by removing the surface oxide film by mechanical mill shaping or jet milling, and then by sieving.

[0018] In one embodiment of the present invention, the silicon composite material and the graphite are classified so that the particle size ratio of the silicon secondary particles to the graphite particles is 1:10 to 1:5. In step S3, the particle size ratio of the silicon composite material to the graphite is 1:10 to 1:5. If the particle size ratio is lower than 1:5, the silicon particles will expand violently after lithium insertion during the cycle process, destroying the arrangement structure of the surrounding graphite particles, and the cycle stability of the pole piece will decrease; if it exceeds 1:10, the silicon particles will be too small or the graphite particles will be too large, and the specific surface area of ​​the silicon particles will be too large, resulting in excessive consumption of electrolyte, leading to accelerated attenuation in the later stage of the cycle; if the graphite particles are too large, the conductivity of the pole piece will decrease. The optimal range of the particle size ratio of the silicon secondary particles to the graphite particles is preferably 1:8 to 1:6.

[0019] In one embodiment of the present invention, in step S3, the negative electrode current collector comprises copper foil, nickel foil, or a copper-nickel alloy.

[0020] In one embodiment of the present invention, in step S3, the effective mass ratio range of the silicon composite, graphite, conductive carbon and polyacrylic acid emulsion (PAA) is 10%:70%:10%:10% to 2%:78%:10%:10%, that is, in the slurry, the mass ratio of the silicon composite, graphite, conductive carbon and polyacrylic acid emulsion is 1:7:1:1 to 0.2:7.8:1:1.

[0021] In one embodiment of the present invention, in step S3, the areal density of the copper foil is 80 g / m 2 ~200g / m 2 Let us assume that.

[0022] In one embodiment of the present invention, in step S3, the roll press density is set to 1.45 g / cc to 1.75 g / cc.

[0023] In one embodiment of the present invention, in step S3, the high temperature in vacuum is in the range of 80°C to 150°C.

[0024] In one embodiment of the present invention, in step S3, the drying time is set to 10 hours to 48 hours.

[0025] In a second aspect, the present invention provides a negative electrode sheet comprising the silicon composite material, which can be produced by the method described above.

[0026] The specific particle size ratio between the silicon composite material and the graphite in the negative electrode sheet is the particle size ratio between the particle size of silicon D50 and the particle size of graphite D50, and is 1:10 to 1:5.

[0027] The negative electrode sheet is used in a lithium battery.

[0028] In a third aspect, the present invention provides a silicon composite material comprising silicon nanoparticles, carbon nanotubes, silicon oxide, lithium oxide and lithium silicate, wherein the carbon nanotubes and silicon nanoparticles are cross-linked with each other to form a three-dimensional network structure, and the three-dimensional network structure is coated with silicon oxide, lithium oxide and lithium silicate to form secondary particles.

[0029] In the secondary particles, the silicon nanoparticles are coated with silicon oxide, lithium oxide, and lithium silicate while maintaining a connection with the carbon nanotubes. When the silicon nanoparticles undergo cyclic expansion, they are buffered under the coating of silicon oxide, lithium oxide, and lithium silicate, which inhibits cyclic expansion while further constraining the carbon nanotubes and preventing separation between the silicon nanoparticles.

[0030] In one embodiment of the present invention, the carbon nanotubes are single-walled carbon nanotubes or multi-walled carbon nanotubes. The single-walled carbon nanotubes preferably have an average diameter of 0.5-5 nm and a length of 10 nm-200 μm. The multi-walled carbon nanotubes preferably have an average diameter of 5-20 nm and a length of 10 nm-200 μm. In addition to maintaining the structural stability of the secondary particles, the conventional step of carbon coating of silicon-oxygen particles to provide ion conduction paths and improve electrical conductivity can be omitted.

[0031] In one embodiment of the present invention, the silicon nanoparticles have an average particle size of 10 to 100 nm.

[0032] In one embodiment of the present invention, the chemical formula of the silicon oxide is SiO x where 1≦x≦2, and x is the SiO x are the independent variables.

[0033] The lithium silicate is a reaction product of lithium and silicon oxide, and Li 4 SiO 4 , Li 2 SiO 3 and Li 2 S 2 O 5 It is a mixture of.

[0034] The lithium oxide has the chemical formula Li 2 O, which is the reaction product of lithium and silicon oxide.

[0035] In one embodiment of the present invention, the silicon / carbon nanotube / silicon oxide / lithium oxide / lithium silicate composite material is a secondary particle, and the average particle diameter of the secondary particle is 2-20 μm. If the particle diameter is smaller than 2 μm, the specific surface area of ​​the particle is too large, which consumes excess electrolyte during cycling, causing accelerated decay in later cycles. If the particle diameter is larger than 20 μm, the volume change due to particle expansion is too large, which destroys the negative electrode sheet structure. More preferably, the average particle diameter is 5-10 μm.

[0036] The silicon composite material is produced by steps S1 and S2 of the method for producing a negative electrode sheet containing the silicon composite material.

[0037] In a fourth aspect, the present invention provides a method for producing a pharmaceutical composition comprising the steps of: S1, adding silicon nanoparticles, carbon nanotubes, a silane coupling agent and a dispersant to an organic solvent, stirring uniformly, and spray-drying to obtain a mixed powder, and then carbonizing the mixed powder at high temperature and ball-milling to obtain a silicon / carbon nanotube / silicon-oxygen composite; S2, activating the silicon / carbon nanotube / silicon-oxygen composite, mixing the activated silicon / carbon nanotube / silicon-oxygen composite with a lithium source, ball milling to obtain a mixture, heat-treating the mixture, and classifying the heat-treated mixture to obtain the secondary particles, i.e., the silicon composite material. Effect of the Invention

[0038] Compared with the prior art, the present invention has the following beneficial effects: 1) In the present invention, silicon nanoparticles, carbon nanotubes and silica are dispersed and dried, and then carbonized at high temperature and ball milled to obtain a silicon / carbon nanotube / silicon oxygen composite. The composite is then mixed with a lithium source, stirred in a ball mill, heat treated and sieved to obtain nanosilicon / carbon nanotube / silicon oxide / lithium oxide / lithium silicate composite secondary particles. The composite is mixed with graphite in a specific particle size ratio to prepare a negative electrode sheet, which fully exerts the high gram capacity of silicon, improves electrical conductivity, and prevents the irreversible side reaction between silicon oxygen and lithium from occurring early, thereby ensuring the initial coulombic efficiency of the battery; 2) The volume expansion of nanosilicon due to lithium insertion is suppressed in the secondary silicon particles, and the graphite particles also play a role in buffering the expansion of the secondary silicon particles, so the volume expansion of this negative electrode sheet is significantly reduced; 3) The battery made of the composite material produced by the present invention has excellent cycle stability, small volume expansion, and excellent rate performance, and can be applied to the automotive field; 4) The present invention has a simple process, omits the CVD coating carbon layer step, is easy to control and has good reproducibility, and provides a new solution for improving the energy density of automotive batteries.

[0039] The features and performance of the present invention are further illustrated by the following examples and their accompanying drawings. [Brief description of the drawings]

[0040] [Figure 1] FIG. 2 is a schematic diagram of the secondary particle structure of the silicon composite material of Example 1. [Diagram 2] FIG. 2 is a surface SEM backscatter diagram of the silicon composite material of Example 1. [Diagram 3] FIG. 2 is a SEM backscattered image of the negative electrode sheet of Example 1 after roll pressing. [Figure 4] FIG. 13 is an SEM backscattered image of the negative electrode sheet of Comparative Example 2 after roll pressing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0041] Here, 1 is silicon nanoparticles, 2 is carbon nanotubes, and 3 is silicon oxide, lithium oxide, and lithium silicate.

[0042] The present invention will be described in detail below with reference to examples. The following examples are provided to facilitate a person skilled in the art to further understand the present invention, but are not intended to limit the present invention in any manner. However, those skilled in the art may make some adjustments and improvements without departing from the concept of the present invention. All of these fall within the scope of protection of the present invention.

[0043] Example 1 (1) Prepare nanosilicon / carbon nanotube / silicon-oxygen composite: To 100 g of the organic solvent N-methylpyrrolidone, 1 g of nanosilicon, 0.05 g of carbon nanotubes, 1 g of alkyleneiminoalkenyldimethylsilane, and 0.1 g of polyethylene glycol with a molecular weight of 900 are added in that order, stirred and mixed uniformly, and spray-dried to obtain a mixed powder. This mixed powder is then high-temperature carbonized at 600°C for 5 hours and ball-milled to obtain a nanosilicon / carbon nanotube / silicon-oxygen composite.

[0044] (2) Supplying lithium to the silicon / carbon nanotube / silicon-oxygen composite: The activator (a mixture of 0.15M HCl, 0.05M HF and 0.05M sodium nitrate) and the nanosilicon / carbon nanotube / silicon oxygen composite were mixed uniformly at room temperature for 10 hours, then dried at 90°C for 8 hours, heat-treated at 550°C for 6 hours, and finally cooled to room temperature under Ar gas protection. The powder obtained by cooling and the lithium source (a mixture of 50wt% lithium sulfate and 50wt% lithium nitrate) were mixed and stirred uniformly at room temperature for 5 hours, then heated at 3000°C for 1 hour under vacuum, and cooled to room temperature under Ar gas protection. The obtained powder was mechanically milled to remove the surface oxide film, and then sieved to obtain the silicon / carbon nanotube / silicon oxide / lithium oxide / lithium silicate composite material, also known as silicon secondary particles. Figure 1 is a schematic diagram of the secondary particle structure of the silicon composite material provided in this embodiment, in which carbon nanotubes and silicon nanoions are cross-linked with each other to form a three-dimensional structure, and silicon oxide, lithium oxide and lithium silicate coat the three-dimensional network structure to form secondary particles. Figure 2 is a surface SEM backscattering diagram of the silicon composite material provided in this embodiment, and backscattered electron imaging shows that the particles are shiny and the surface is all silicon particles. The particles are circular and the particle size is less than 10 μm.

[0045] (3) Prepare the silicon composite material as a negative electrode sheet: The silicon composite material and graphite are classified so that the particle size ratio of the silicon secondary particles to the graphite particles is 1:8 (the particle size of the silicon secondary particles at 50% by volume is 3.1 μm, and the particle size of the graphite particles at 50% by volume is 24.2 μm). The silicon composite material, graphite, conductive carbon, and 0.6% polyacrylic acid emulsion (PAA) are mixed in an effective mass ratio of 1:7:1:1 to prepare a slurry, which is then cooled to a surface density of 100 g / m. 2The negative electrode sheet was prepared by applying the above-mentioned mixture to a copper foil having a thickness of 10 μm, rolling pressing the mixture to a roll pressing density of 1.6 g / cc, and drying the mixture in a vacuum at 120° C. for 24 hours. FIG. 3 shows the SEM backscattering image of the negative electrode sheet provided in this embodiment after rolling. The silicon secondary particles are located in the gaps between the graphite particles, and when the silicon particles expand due to lithium insertion, the surrounding graphite particles provide a certain restraining force to suppress the volume expansion. At the same time, the volume expansion of the particles does not lead to the rearrangement of the graphite particles, ensuring the structural stability of the pole pieces during the cycle process.

[0046] Example 2 (1) Prepare nanosilicon / carbon nanotube / silicon-oxygen composite: To 100 g of the organic solvent acetone, 1.5 g of nanosilicon, 0.03 g of carbon nanotubes, 1.5 g of alkyleneiminoalkenyldimethylsilane, and 0.2 g of polyethylene glycol with a molecular weight of 900 are added in that order, stirred and mixed uniformly, and spray-dried to obtain a mixed powder. This mixed powder is then high-temperature carbonized at 500°C for 6 hours and ball-milled to obtain a nanosilicon / carbon nanotube / silicon-oxygen composite.

[0047] (2) Supplying lithium to the silicon / carbon nanotube / silicon-oxygen composite: The activator (a mixture of 0.25M HCl, 0.02M HF and 0.02M sodium nitrate) and the nanosilicon / carbon nanotube / silicon oxygen composite were mixed uniformly at room temperature for 8 hours, then dried at 80°C for 10 hours, heat-treated at 500°C for 7 hours, and finally cooled to room temperature under Ar gas protection. The powder obtained by cooling and the lithium source (a mixture of 50wt% lithium sulfate and 50wt% lithium nitrate) were mixed and stirred uniformly at room temperature for 6 hours, then heated at 3500°C for 1.5 hours under vacuum, and cooled to room temperature under Ar gas protection. The obtained powder was jet milled to remove the surface oxide film, and then sieved to obtain a silicon / carbon nanotube / silicon oxide / lithium oxide / lithium silicate composite material.

[0048] (3) Prepare the silicon composite material as a negative electrode sheet: The silicon composite material and graphite are classified so that the particle size ratio of the silicon secondary particles to the graphite particles is 1:7 (the particle size of the silicon secondary particles at 50% by volume is 3.5 μm, and the particle size of the graphite particles at 50% by volume is 24.2 μm). The silicon composite material, graphite, conductive carbon, and 0.6% polyacrylic acid emulsion (PAA) are mixed in an effective mass ratio of 1:7:1:1 to prepare a slurry, which is then cooled to a surface density of 100 g / m. 2 The mixture was applied to a copper foil having a thickness of 10 μm, roll pressed to a roll press density of 1.6 g / cc, and dried in a vacuum at 120° C. for 24 hours to prepare a negative electrode sheet.

[0049] Example 3 (1) Prepare nanosilicon / carbon nanotube / silicon-oxygen composite: To 100 g of carbon tetrachloride, 2 g of nanosilicon, 0.02 g of carbon nanotubes, 1.8 g of alkyleneiminoalkenyldimethylsilane, and 0.6 g of polyethylene glycol with a molecular weight of 900 are added in that order, stirred and mixed uniformly, and spray-dried to obtain a mixed powder. This mixed powder is then high-temperature carbonized at 550°C for 5.5 hours and ball-milled to obtain a nanosilicon / carbon nanotube / silicon-oxygen composite.

[0050] (2) Supplying lithium to the silicon / carbon nanotube / silicon-oxygen composite: The activator (a mixture of 0.2M HCl, 0.03M HF and 0.03M sodium nitrate) and the nanosilicon / carbon nanotube / silicon oxygen composite were mixed uniformly at room temperature for 9 hours, then dried at 85°C for 9 hours, heat-treated at 600°C for 6 hours, and finally cooled to room temperature under Ar gas protection. The powder obtained by cooling and the lithium source (a mixture of 50wt% lithium nitrate and 50wt% lithium halide) were mixed and stirred uniformly at room temperature for 7 hours, then heated at 2500°C for 2 hours under vacuum, and cooled to room temperature under Ar gas protection. The obtained powder was jet milled to remove the surface oxide film, and then sieved to obtain a silicon / carbon nanotube / silicon oxide / lithium oxide / lithium silicate composite material.

[0051] (3) Prepare the silicon composite material as a negative electrode sheet: The silicon composite material and graphite are classified so that the particle size ratio of the silicon secondary particles to the graphite particles is 1:6 (the particle size of the silicon secondary particles at 50% by volume is 6.1 μm, and the particle size of the graphite particles at 50% by volume is 24.2 μm). The silicon composite material, graphite, conductive carbon, and 0.6% polyacrylic acid emulsion (PAA) are mixed in an effective mass ratio of 1:7:1:1 to prepare a slurry, which is then cooled to a surface density of 100 g / m. 2 The mixture was applied to a copper foil having a thickness of 10 μm, roll pressed to a roll press density of 1.6 g / cc, and dried in a vacuum at 120° C. for 24 hours to prepare a negative electrode sheet.

[0052] Example 4 (1) Prepare nanosilicon / carbon nanotube / silicon-oxygen composite: To 100 g of the organic solvent N-methylpyrrolidone, 1 g of nanosilicon, 0.05 g of carbon nanotubes, 1 g of alkyleneiminoalkenyldimethylsilane, and 0.1 g of polyethylene glycol with a molecular weight of 900 are added in that order, stirred and mixed uniformly, and spray-dried to obtain a mixed powder. This mixed powder is then high-temperature carbonized at 600°C for 5 hours and ball-milled to obtain a nanosilicon / carbon nanotube / silicon-oxygen composite.

[0053] (2) Supplying lithium to the silicon / carbon nanotube / silicon-oxygen composite: The activator (a mixture of 0.15M HCl, 0.05M HF and 0.05M sodium nitrate) and the nanosilicon / carbon nanotube / silicon oxygen composite were mixed uniformly at room temperature for 10 hours, then dried at 90°C for 8 hours, heat-treated at 550°C for 6 hours, and finally cooled to room temperature under Ar gas protection. The powder obtained by cooling and the lithium source (a mixture of 50wt% lithium sulfate and 50wt% lithium nitrate) were mixed and stirred uniformly at room temperature for 5 hours, then heated at 3000°C for 1 hour under vacuum, and cooled to room temperature under Ar gas protection. The obtained powder was mechanically milled to remove the surface oxide film, and then sieved to obtain the silicon / carbon nanotube / silicon oxide / lithium oxide / lithium silicate composite material, also known as silicon secondary particles.

[0054] (3) Prepare the silicon composite material as a negative electrode sheet: The silicon composite material and graphite are classified so that the particle size ratio of the silicon secondary particles to the graphite particles is 1:8 (the particle size of the silicon secondary particles at 50% by volume is 3.1 μm, and the particle size of the graphite particles at 50% by volume is 24.2 μm). The silicon composite material, graphite, conductive carbon, and 0.6% polyacrylic acid emulsion (PAA) are mixed in an effective mass ratio of 6:74:10:10 to prepare a slurry, which is then cooled to a surface density of 100 g / m. 2 The mixture was applied to a copper foil having a thickness of 10 μm, roll pressed to a roll press density of 1.6 g / cc, and dried in a vacuum at 120° C. for 24 hours to prepare a negative electrode sheet.

[0055] Example 5 (1) Prepare nanosilicon / carbon nanotube / silicon-oxygen composite: To 100 g of the organic solvent N-methylpyrrolidone, 1 g of nanosilicon, 0.05 g of carbon nanotubes, 1 g of alkyleneiminoalkenyldimethylsilane, and 0.1 g of polyethylene glycol with a molecular weight of 900 are added in that order, stirred and mixed uniformly, and spray-dried to obtain a mixed powder. This mixed powder is then high-temperature carbonized at 600°C for 5 hours and ball-milled to obtain a nanosilicon / carbon nanotube / silicon-oxygen composite.

[0056] (2) Supplying lithium to the silicon / carbon nanotube / silicon-oxygen composite: The activator (a mixture of 0.15M HCl, 0.05M HF and 0.05M sodium nitrate) and the nanosilicon / carbon nanotube / silicon oxygen composite were mixed uniformly at room temperature for 10 hours, then dried at 90°C for 8 hours, heat-treated at 550°C for 6 hours, and finally cooled to room temperature under Ar gas protection. The powder obtained by cooling and the lithium source (a mixture of 50wt% lithium sulfate and 50wt% lithium nitrate) were mixed and stirred uniformly at room temperature for 5 hours, then heated at 3000°C for 1 hour under vacuum, and cooled to room temperature under Ar gas protection. The obtained powder was mechanically milled to remove the surface oxide film, and then sieved to obtain the silicon / carbon nanotube / silicon oxide / lithium oxide / lithium silicate composite material, also known as silicon secondary particles.

[0057] (3) Prepare the silicon composite material as a negative electrode sheet: The silicon composite material and graphite are classified so that the particle size ratio of the silicon secondary particles to the graphite particles is 1:8 (the particle size of the silicon secondary particles at 50% by volume is 3.1 μm, and the particle size of the graphite particles at 50% by volume is 24.2 μm). The silicon composite material, graphite, conductive carbon, and 0.6% polyacrylic acid emulsion (PAA) are mixed in an effective mass ratio of 2:78:10:10 to prepare a slurry, which is then cooled to a surface density of 100 g / m. 2 The mixture was applied to a copper foil having a thickness of 10 μm, roll pressed to a roll press density of 1.6 g / cc, and dried in a vacuum at 120° C. for 24 hours to prepare a negative electrode sheet.

[0058] Comparative Example 1 (1) Fabricate a silicon composite material: To 100 g of the organic solvent acetone, 1.5 g of nanosilicon, 0.03 g of carbon nanotubes, 1.5 g of alkyleneiminoalkenyldimethylsilane, and 0.2 g of polyethylene glycol with a molecular weight of 900 are added in that order, stirred and mixed uniformly, and spray-dried to obtain a mixed powder. This mixed powder is then high-temperature carbonized at 500°C for 6 hours and ball-milled to obtain a nanosilicon / carbon nanotube / silicon-oxygen composite.

[0059] (2) Prepare the silicon composite material as a negative electrode sheet: The silicon composite material and graphite are classified so that the particle size ratio of the nanosilicon / carbon nanotube / silicon-oxygen composite to the graphite particles is 1:7 (the particle size of the silicon secondary particles at 50% by volume is 3.5 μm, and the particle size of the graphite particles at 50% by volume is 24.2 μm). The silicon composite material, graphite, conductive carbon, and 0.6% polyacrylic acid emulsion (PAA) are mixed in an effective mass ratio of 1:7:1:1 to prepare a slurry, which is then cooled to a surface density of 100 g / m. 2 The mixture was applied to a copper foil having a thickness of 10 μm, roll pressed to a roll press density of 1.6 g / cc, and dried in a vacuum at 120° C. for 24 hours to prepare a negative electrode sheet.

[0060] Comparative Example 2 (1) Prepare nanosilicon / carbon nanotube / silicon-oxygen composite: To 100 g of carbon tetrachloride, 2 g of nanosilicon, 0.02 g of carbon nanotubes, 1.8 g of alkyleneiminoalkenyldimethylsilane, and 0.6 g of polyethylene glycol with a molecular weight of 900 are added in that order, stirred and mixed uniformly, and spray-dried to obtain a mixed powder. This mixed powder is then high-temperature carbonized at 550°C for 5.5 hours and ball-milled to obtain a nanosilicon / carbon nanotube / silicon-oxygen composite.

[0061] (2) Supplying lithium to the silicon / carbon nanotube / silicon-oxygen composite: The activator (a mixture of 0.2M HCl, 0.03M HF and 0.03M sodium nitrate) and the nanosilicon / carbon nanotube / silicon oxygen composite were mixed uniformly at room temperature for 9 hours, then dried at 85°C for 9 hours, heat-treated at 600°C for 6 hours, and finally cooled to room temperature under Ar gas protection. The powder obtained by cooling and the lithium source (a mixture of 50wt% lithium nitrate and 50wt% lithium halide) were mixed and stirred uniformly at room temperature for 7 hours, then heated at 2500°C for 2 hours under vacuum, and cooled to room temperature under Ar gas protection. The obtained powder was jet milled to remove the surface oxide film, and then sieved to obtain a silicon / carbon nanotube / silicon oxide / lithium oxide / lithium silicate composite material.

[0062] (3) Prepare the silicon composite material as a negative electrode sheet: The silicon composite material and graphite are classified so that the particle size ratio of the silicon secondary particles to the graphite particles is 1:3 (the particle size of the silicon secondary particles at 50% by volume is 8.1 μm, and the particle size of the graphite particles at 50% by volume is 24.2 μm). The silicon composite material, graphite, conductive carbon, and 0.6% polyacrylic acid emulsion (PAA) are mixed in an effective mass ratio of 1:7:1:1 to prepare a slurry, which is then cooled to a surface density of 100 g / m. 2 The negative electrode sheet was prepared by applying the above-mentioned mixture to a copper foil having a thickness of 10 μm, rolling pressing the mixture to a roll pressing density of 1.6 g / cc, and drying the mixture in a vacuum at 120° C. for 24 hours. FIG. 4 shows the SEM backscattering pattern of the negative electrode sheet provided in this comparative example after rolling. In the figure, there are silicon secondary particles with a relatively large particle size (about 8 μm). During the cycle process, the silicon particles expand rapidly (volume expansion rate of about 200%), and the surrounding graphite particles cannot effectively suppress the volume expansion. This rapid expansion causes the distribution of the surrounding graphite particles to change, destroying the conventional pole piece arrangement structure and damaging the conductive network.

[0063] Comparative Example 3 (1) Prepare nanosilicon / carbon nanotube / silicon-oxygen composite: To 100 g of carbon tetrachloride, 2 g of nanosilicon, 0.02 g of carbon nanotubes, 1.8 g of alkyleneiminoalkenyldimethylsilane, and 0.6 g of polyethylene glycol with a molecular weight of 900 are added in that order, stirred and mixed uniformly, and spray-dried to obtain a mixed powder. This mixed powder is then high-temperature carbonized at 550°C for 5.5 hours and ball-milled to obtain a nanosilicon / carbon nanotube / silicon-oxygen composite.

[0064] (2) Supplying lithium to the silicon / carbon nanotube / silicon-oxygen composite: The activator (a mixture of 0.2M HCl, 0.03M HF and 0.03M sodium nitrate) and the nanosilicon / carbon nanotube / silicon oxygen composite were mixed uniformly at room temperature for 9 hours, then dried at 85°C for 9 hours, heat-treated at 600°C for 6 hours, and finally cooled to room temperature under Ar gas protection. The powder obtained by cooling and the lithium source (a mixture of 50wt% lithium nitrate and 50wt% lithium halide) were mixed and stirred uniformly at room temperature for 7 hours, then heated at 2500°C for 2 hours under vacuum, and cooled to room temperature under Ar gas protection. The obtained powder was jet milled to remove the surface oxide film, and then sieved to obtain a silicon / carbon nanotube / silicon oxide / lithium oxide / lithium silicate composite material.

[0065] (3) Prepare the silicon composite material as a negative electrode sheet: The silicon composite material and graphite are classified so that the particle size ratio of the silicon secondary particles to the graphite particles is 1:11 (the particle size of the silicon secondary particles at 50% by volume is 2.2 μm, and the particle size of the graphite particles at 50% by volume is 24.2 μm). The silicon composite material, graphite, conductive carbon, and 0.6% polyacrylic acid emulsion (PAA) are mixed in an effective mass ratio of 1:7:1:1 to prepare a slurry, which is then cooled to a surface density of 100 g / m. 2 The mixture was applied to a copper foil having a thickness of 10 μm, roll pressed to a roll press density of 1.6 g / cc, and dried in a vacuum at 120° C. for 24 hours to prepare a negative electrode sheet. 。

[0066] Comparative Example 4 (1) Prepare nanosilicon / carbon nanotube / silicon-oxygen composite: To 100 g of carbon tetrachloride, 2 g of nanosilicon, 0.02 g of carbon nanotubes, 1.8 g of alkyleneiminoalkenyldimethylsilane, and 0.6 g of polyethylene glycol with a molecular weight of 900 are added in that order, stirred and mixed uniformly, and spray-dried to obtain a mixed powder. This mixed powder is then high-temperature carbonized at 550°C for 5.5 hours and ball-milled to obtain a nanosilicon / carbon nanotube / silicon-oxygen composite.

[0067] (2) Supplying lithium to the silicon / carbon nanotube / silicon-oxygen composite: The activator (a mixture of 0.2M HCl, 0.03M HF, and 0.03M sodium nitrate) and the nanosilicon / carbon nanotube / silicon oxygen composite were mixed uniformly at room temperature for 9 hours, then dried at 85°C for 9 hours, heat-treated at 600°C for 6 hours, and finally cooled to room temperature under Ar gas protection. The powder obtained by cooling and the lithium source (a mixture of 50wt% lithium nitrate and 50wt% lithium halide) were mixed and stirred uniformly at room temperature for 7 hours, then heated at 2,000°C for 0.5 hours under vacuum, and cooled to room temperature under Ar gas protection. The obtained powder was shaped by a jet mill to remove the surface oxide film, and then sieved to obtain a silicon / carbon nanotube / silicon oxide / lithium oxide / lithium silicate composite material.

[0068] (3) Prepare the silicon composite material as a negative electrode sheet: The silicon composite material and graphite are classified so that the particle size ratio of the silicon secondary particles to the graphite particles is 1:6 (the particle size of the silicon secondary particles at 50% by volume is 6.1 μm, and the particle size of the graphite particles at 50% by volume is 24.2 μm). The silicon composite material, graphite, conductive carbon, and 0.6% polyacrylic acid emulsion (PAA) are mixed in an effective mass ratio of 1:7:1:1 to prepare a slurry, which is then cooled to a surface density of 100 g / m. 2The mixture was applied to a copper foil having a thickness of 10 μm, roll pressed to a roll press density of 1.6 g / cc, and dried in a vacuum at 120° C. for 24 hours to prepare a negative electrode sheet.

[0069] Comparative Example 5 (1) Preparation of nanosilicon / carbon nanotube / silicon-oxygen composite: To 100 g of carbon tetrachloride, 2 g of nanosilicon, 0.02 g of carbon nanotubes, 1.8 g of alkyleneiminoalkenyldimethylsilane, and 0.6 g of polyethylene glycol with a molecular weight of 900 are added in that order, stirred and mixed uniformly, and spray-dried to obtain a mixed powder. This mixed powder is then high-temperature carbonized at 550°C for 5.5 hours and ball-milled to obtain a nanosilicon / carbon nanotube / silicon-oxygen composite.

[0070] (2) Supplying lithium to the silicon / carbon nanotube / silicon-oxygen composite: The activator (a mixture of 0.2M HCl, 0.03M HF and 0.03M sodium nitrate) and the nanosilicon / carbon nanotube / silicon oxygen composite were mixed uniformly at room temperature for 9 hours, then dried at 85°C for 9 hours, heat-treated at 600°C for 6 hours, and finally cooled to room temperature under Ar gas protection. The powder obtained by cooling and the lithium source (a mixture of 50wt% lithium nitrate and 50wt% lithium halide) were mixed and stirred uniformly at room temperature for 7 hours, then heated at 3500°C for 5 hours under vacuum, and cooled to room temperature under Ar gas protection. The obtained powder was jet milled to remove the surface oxide film, and then sieved to obtain a silicon / carbon nanotube / silicon oxide / lithium oxide / lithium silicate composite material.

[0071] (3) Prepare the silicon composite material as a negative electrode sheet: The silicon composite material and graphite are classified so that the particle size ratio of the silicon secondary particles to the graphite particles is 1:6 (the particle size of the silicon secondary particles at 50% by volume is 6.1 μm, and the particle size of the graphite particles at 50% by volume is 24.2 μm). The silicon composite material, graphite, conductive carbon, and 0.6% polyacrylic acid emulsion (PAA) are mixed in an effective mass ratio of 1:7:1:1 to prepare a slurry, which is then cooled to a surface density of 100 g / m. 2 The mixture was applied to a copper foil having a thickness of 10 μm, roll pressed to a roll press density of 1.6 g / cc, and dried in a vacuum at 120° C. for 24 hours to prepare a negative electrode sheet.

[0072] Example 6, Application Performance Detection: The steps used for assembling and testing the negative electrode sheets prepared in the above examples and comparative examples are as follows:

[0073] The counter electrode is a metallic lithium piece with a purity of 99.9%, and the electrolyte is a solution of 1.1 mol lithium hexafluorophosphate (LiPF6) in ethylene carbonate (EC) / methyl ethyl carbonate (EMC) / diethyl carbonate (DEC) (volume ratio 3:5:2). After drying the negative electrode sheet, metallic lithium sheet, battery case, and separator, the electrolyte is added in a glove box protected by argon gas to assemble a button-type lithium-ion battery. A charge-discharge cycle test is performed on the battery, with the charge voltage cut off at 2.0 V, the discharge voltage cut off at 0.005 V, and the charge-discharge cycle multiplier at 0.1 C. The data on the initial lithium insertion capacity and lithium desorption capacity, and the lithium desorption capacity after 50 cycles are shown in Table 1.

[0074] [Table 1]

[0075] As can be seen from Table 1, the silicon composite materials prepared in Examples 1-3 of the present invention exhibit high coulombic efficiency, low volume expansion, and good cycle characteristics.

[0076] The specific embodiments of the present invention have been described above. However, the present invention is not limited to the above-mentioned specific embodiments, and those skilled in the art may make various modifications or changes within the scope of the claims, which do not affect the essence of the present invention. [Explanation of symbols]

[0077] 1. Silicon nanoparticles 2. Carbon nanotubes 3. Silicon oxide, lithium oxide, lithium silicate

Claims

1. A method for producing a negative electrode sheet containing a silicon composite material, the negative electrode sheet further containing graphite, and a particle size ratio of the silicon composite material to the graphite is 1:10 to 1:5; S1, adding silicon nanoparticles, carbon nanotubes, a silane coupling agent and a dispersant to an organic solvent, stirring uniformly, and spray-drying to obtain a mixed powder, and carbonizing the mixed powder at high temperature and ball-milling to obtain a silicon / carbon nanotube / silicon-oxygen composite; S2, activating the silicon / carbon nanotube / silicon-oxygen composite, mixing the activated silicon / carbon nanotube / silicon-oxygen composite with a lithium source, and ball milling to obtain a mixture, heat-treating the mixture and keeping it warm for 1 to 2 hours, and classifying the heat-treated mixture to obtain secondary particles, i.e., the silicon composite material; S3: mixing the silicon composite material with graphite, conductive carbon and polyacrylic acid emulsion to prepare a slurry, which is applied to a negative electrode current collector, roll-pressed, and then dried under high temperature and vacuum to prepare a negative electrode sheet; A method for producing a negative electrode sheet, comprising:

2. 2. The method for producing a negative electrode sheet according to claim 1, wherein in step S3, the negative electrode current collector comprises copper foil, nickel foil, or a copper-nickel alloy.

3. 2. The method for producing a negative electrode sheet according to claim 1, wherein in step S3, a mass ratio of the silicon composite material, the graphite, the conductive carbon and the polyacrylic acid emulsion in the slurry is 1:7:1:1 to 0.2:7.8:1:

1.

4. 2. The method for producing a negative electrode sheet according to claim 1, wherein in step S1, the weight ratio of the silicon nanoparticles, the carbon nanotubes, the silane coupling agent, the dispersant, and the organic solvent is (1-5):(0.01-0.05):(1-5):(0.1-1):

100.

5. 2. The method for producing a negative electrode sheet according to claim 1, wherein in step S2, the lithium source includes a solid-phase and / or liquid-phase lithium source, and the liquid-phase lithium source includes one or more of lithium sulfate, lithium nitrate, and lithium halide.

6. 2. The method for producing a negative electrode sheet according to claim 1, wherein in step S2, the activation step includes uniformly mixing an activator with the silicon / carbon nanotube / silicon-oxygen composite, and the uniformly mixed product is dried and heat-treated, and then cooled to room temperature under gas protection, and the activator contains one or more of 0.1-3M HF, 0.1-1M HCl, 0.1-1M sodium nitrate, and 0.1-1M potassium permanganate.

7. A negative electrode sheet comprising a silicon composite material produced by the method according to any one of claims 1 to 6, said negative electrode sheet being used in a lithium battery.

8. A silicon composite material applicable to the method for producing a negative electrode sheet according to any one of claims 1 to 6, comprising silicon nanoparticles, carbon nanotubes, silicon oxide, lithium oxide, and lithium silicate, the carbon nanotubes and silicon nanoparticles being cross-linked to each other to form a three-dimensional network structure, and the three-dimensional network structure being coated with silicon oxide, lithium oxide, and lithium silicate to form secondary particles.

9. The silicon composite material according to claim 8, characterized in that the secondary particles have an average particle size of 2 to 20 μm.

Citation Information

Patent Citations

  • Silicon-carbon nanotube-carbon silicon oxide composite, preparation method and application

    CN107658452A

  • Negative electrode material with multiple coating structures as well as preparation method and application of negative electrode material

    CN110993949A

  • Silicon-carbon composite material and preparation method and application thereof

    CN111048764A

  • Nonaqueous secondary battery

    JP2012059721A

  • Negative electrode for non-aqueous secondary battery, and non-aqueous secondary battery

    WO2012018035A1